PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS KEARIFAN LOKAL LOPO PADA MATERI BANGUN DATAR KELAS 3 DI SD NEGERI NOEBESA KABUPATEN TIMOR TENGAH SELATAN - Sumiriati Nubatonis; Yulsy Marselina Nitte; Abdurrahman Abdullah (STKIP Subang, 2025)
This study aims to develop a learning medium based on local wisdom, namely the “Lopo”, to integrate cultural values into the learning process. The integration of local culture is considered essential to strengthen students’ cultural identity and enhance the relevance of learning materials to their daily lives. The research employed a Research and Development (R&D) approach using the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The participants of this study were third-grade students from an elementary school in Timor Tengah Selatan Regency. The developed learning media was evaluated by experts in material, media, and language, all of whom provided very positive assessments. The validation results showed that material experts rated the media at 75% (feasible), language experts at 97.2% (highly feasible), media experts at 94.4% (highly feasible), teachers at 82.81% (very good), and students at 97.50% (highly feasible). Furthermore, students’ learning achievement increased from 73.87% before using the media to 89.47% after implementation. These findings indicate that the “Lopo”-based local wisdom learning media is feasible, attractive, practical, and effective for teaching flat shapes in elementary schools.